2022
DOI: 10.1111/clr.14000
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term results in three‐dimensional, complex bone augmentation procedures with customized titanium meshes

Abstract: Objectives: Complex, three-dimensional bony defects still represent challenging situations in routine implant dentistry. The aim of this study was to evaluate implant survival in customized bone regeneration using a patient-specific titanium mesh.Material and Methods: Patients (n = 21, implants 36) who had obtained an augmentation procedure with patient-specific titanium mesh were examined after 5.7 ± 0.38 years. Survival rate, clinical parameters for periimplantitis (Bleeding on Probing [BOP] and suppuration)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Nevertheless, a recent systematic review did not find a significant difference in exposure rates between conventional and customized meshes, 125 whereas another review did see this difference 126 . For (customized) titanium meshes, most reports analyzed horizontal augmentation of a maximum of 5–7 mm vertically and 4–5 mm in horizontal height, or did not give exact data on the augmented volume 121,124,127–131 . In one case series, a vertical and horizontal gain of up to 9 mm with an exposure rate of 1/10 cases was reported 132 .…”
Section: Stabilization Of Particulated Graftsmentioning
confidence: 97%
See 3 more Smart Citations
“…Nevertheless, a recent systematic review did not find a significant difference in exposure rates between conventional and customized meshes, 125 whereas another review did see this difference 126 . For (customized) titanium meshes, most reports analyzed horizontal augmentation of a maximum of 5–7 mm vertically and 4–5 mm in horizontal height, or did not give exact data on the augmented volume 121,124,127–131 . In one case series, a vertical and horizontal gain of up to 9 mm with an exposure rate of 1/10 cases was reported 132 .…”
Section: Stabilization Of Particulated Graftsmentioning
confidence: 97%
“…121 For improved surgeons' and patients' reported outcomes, prefabricated patient-specific meshes were introduced 120 and used with promising results, including less exposure (0%-33%) and shorter operation times (Figure 5). 55,114,[122][123][124] Nevertheless, a recent systematic review did not find a significant difference in exposure rates between conventional and customized meshes, 125 whereas another review did see this difference. 126 For (customized) titanium meshes, most reports analyzed horizontal augmentation of a maximum of 5-7 mm vertically and 4-5 mm in horizontal height, or did not give exact data on the augmented volume.…”
Section: Titanium Meshesmentioning
confidence: 99%
See 2 more Smart Citations
“…There were shorter operative times and reduced risk of postoperative infections among these serial cases. Cucchi and colleagues [10][11][12] reported a series of clinical studies stating that sufficient augmentation volume and satisfactory clinical outcome could be obtained using customized mesh. Li and colleagues 13 reported that coupling customized mesh with GBR surgery increases the augmentation of alveolar bone by providing osteogenic conditions for the healing stage.…”
Section: Introductionmentioning
confidence: 99%